Integrative Network Pharmacology and In Silico Analysis of Sauropus androgynus Active Compounds as Potential Supplements Against Childhood Stunting - Arwansyah, Arwansyah; Sabang, Sri Mulyani; Tahril, Tahril; Arif, Abdur Rahman; Sakung, Jamaludin Musa; Zubair, Muhammad Sulaiman; Wahyudi, Setyanto Tri (Universitas Gadjah Mada, 2026)
Stunted growth remains a critical public health concern, particularly in developing regions. This study investigates the potential of active compounds derived from Sauropus androgynus as dietary supplements for preventing growth stunting, employing a network pharmacology approach. Fifteen phytochemicals were analyzed, leading to the identification of 11 growth-related target proteins. Among them, protein tyrosine phosphatase nonreceptor type 11 (PTPN11) emerged as a key regulatory protein related to cell growth, as determined by protein-protein interaction network analysis. Functional enrichment and pathway analyses further highlighted the relevance of these targets in growth-related mechanisms. Molecular docking was performed to investigate the molecular interactions between the active compounds of S. androgynous and PTPN11. The findings revealed that all compounds could form a complex at the active site of PTPN11. Furthermore, the top five ligands were subjected to MD simulation to evaluate the structural stability of all complexes. Among them, only two lead compounds, such as paeonol and phenylacetaldehyde, are stable in complex with PTPN11 during simulation. The findings suggest that S. androgynus contains promising active compounds that may serve as functional food supplements for preventing stunted growth, highlighting their potential role in improving child growth outcomes among at-risk populations.